Comparative studies of culture and power - Engelstad, Fredrik (Comparative social research, 2003)
The "cultural turn" in sociology created a new interest in power questions. This has led to a renewed interest in conceptual discussions of power in the field of culture studies, whereas empirical work is still less developed. "Comparative Studies of Culture and Power" sets the focus on the uses of cultural and symbolic means in struggles for hegemony: in politics, music markets, literature and the arts. Gender specific uses of rhetorical techniques is one salient theme, struggles for recognition of rhythm and blues music another. Several articles treat the role of the arts in nation building, as well as the role of public monuments in the acknowledgement of war and terrorism. The analyses relate to cultures all over the Western world.